The Explicit Attitude of Adolescents Towards Peers with Cancer - Hanna Stępniewska-Gębik; Sławomir Trusz (Nicolaus Copernicus University in Toruń, 2020)
The social stigma of cancer is a powerful source of stereotyping and prejudice against people affected by oncology disorders. The research problem is presented in the following question: what is the formal and content characteristic of the stereotype of adolescents with cancer shaped by healthy peers. The cross-sectional included 2,370 high school students in Poland. The frequency analysis of open-ended descriptions and exploratory factor analysis of attributes representing basic domains of human functioning revealed that adolescent cancer patients were characterized in three domains: emotional, social, and physical appearance. Furthermore, cancer was linked with negative explicit prejudice. The obtained results and their practical implications are discussed in light of theories of stigmatization, stereotyping, and prejudice against people with cancer.